An Analysis of COVID-19 Student Learning Loss - Patrinos, Harry Anthony; Vegas, Emiliana; Carter-Rau, Rohan (World Bank, Washington, DC, 2022)
COVID-19 caused significant disruption to the global education system. Early reviews of the first wave of lockdowns and school closures suggested significant learning loss in a few countries. A more recent and thorough analysis of recorded learning loss evidence documented since the beginning of the school closures between March 2020 and March 2022 finds even more evidence of learning loss. Most studies observed increases in inequality where certain demographics of students experienced more significant learning losses than others. But there are also outliers, countries that managed to limit the amount of loss. This review aims to consolidate all the available evidence and documents the empirical findings. Thirty-six robust studies were identified, the majority of which find learning losses on average amounting to 0.17 of a standard deviation, equivalent to roughly a one-half year’s worth of learning. These findings confirm that learning loss is real and significant, even compared to the first year of the pandemic. Further work is needed to increase the quantity of studies produced, and to ascertain the reasons for learning loss and in a few cases mitigation of loss.